2021
DOI: 10.3389/fmed.2021.691712
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Pulses Plus Tacrolimus in Addition to Standard of Care vs. Standard of Care Alone in Patients With Severe COVID-19. A Randomized Controlled Trial

Abstract: Introduction: Severe lung injury is triggered by both the SARS-CoV-2 infection and the subsequent host-immune response in some COVID-19 patients.Methods: We conducted a randomized, single-center, open-label, phase II trial with the aim to evaluate the efficacy and safety of methylprednisolone pulses and tacrolimus plus standard of care (SoC) vs. SoC alone, in hospitalized patients with severe COVID-19. The primary outcome was time to clinical stability within 56 days after randomization.Results: From April 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Tacrolimus has a positive effect on survival in liver transplant patients with symptoms of COVID-19 compared to other immunosuppressants, including cyclosporine and mycophenolate mofetil (65). Nevertheless, there was no improvement in severe COVID-19 patients who received a combination of methylprednisolone pulses and tacrolimus (66).…”
Section: Conventional Synthetic Disease-modifying Antirheumatic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus has a positive effect on survival in liver transplant patients with symptoms of COVID-19 compared to other immunosuppressants, including cyclosporine and mycophenolate mofetil (65). Nevertheless, there was no improvement in severe COVID-19 patients who received a combination of methylprednisolone pulses and tacrolimus (66).…”
Section: Conventional Synthetic Disease-modifying Antirheumatic Drugsmentioning
confidence: 99%
“…Tacrolimus has a positive effect on survival in liver transplant patients with symptoms of COVID-19 compared to other immunosuppressants, including cyclosporine and mycophenolate mofetil ( 65 ). Nevertheless, there was no improvement in severe COVID-19 patients who received a combination of methylprednisolone pulses and tacrolimus ( 66 ). A prospective study demonstrated that a combination of high-dose glucocorticoids, tacrolimus and intravenous cyclophosphamide improved survival in anti-MDA5 + DM patients complicated with ILD.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Whilst antimetabolic drugs seem to have a negative effect [ 104 ], calcineurin inhibitors (e.g. tacrolimus, ciclosporin) and mTOR inhibitors may have a favourable impact on disease course [ [109] , [110] , [111] , [112] ]. Therefore, adjustments to the dose and type of immunosuppression during SARS-CoV-2 infection should be individually tailored based on COVID-19 severity, the specific regimen used, time post-transplant, and the risk of allograft rejection.…”
Section: Risk Stratification and Disease Course Of Sars-cov-2 Infecti...mentioning
confidence: 99%
“…A single small randomized controlled trial of 55 patients with severe COVID-19 indicated that combination therapy with methylprednisolone and tacrolimus resulted in numerically lower all-cause mortality compared with standard treatment. However this difference was not significant and dual therapy was associated with an increased risk of secondary infections [ 111 ].
EASL position Calcineurin inhibitors should not be routinely modified following SARS-CoV-2 infection (exception: see statement on nirmatrelvir/r).
…”
Section: Treatment Of Covid-19 In Patients With Chronic Liver Disease...mentioning
confidence: 99%
“…A total 24 studies demonstrated the beneficial effects of the corticosteroid therapy on the prevention of mortality in the COVID-19 patients 3,7,8,10,12,34,42,43,45,46,48,[50][51][52][53][54][55]57,59,61,63,64,66,67 while 17 studies were reported the increased mortality in the corticosteroid therapy received COVID-19 patients 32,33,[35][36][37][38][39][40][41]44,48,[56][57][58]60,65 while 2 studies reported the neutral effects of the corticosteroid therapy on the prevention of mortality in the COVID-19 patients. 49,62 Four types of corticosteroid were used as single or multiple steroids individually including Methylprednisolone (n = 24), Dexamethasone (n = 6), Hydrocortisone (n = 1), Prednisone (n = 1), corticosteroid used individually including Methylprednisolone and Dexamethasone in the study (n = 6) unknown corticosteroid (n = 5) (Table 1).…”
Section: Basic Characteristics Of the Selected Studiesmentioning
confidence: 99%